Pharmaceutical consultations in oncology: French Society for Oncology Pharmacy (Société Francaise de Pharmacie Oncologique – SFPO) guidelines. Issue 2 (April 2019) - Petit-Jean, Emilie; Correard, Florian; Maillan, Gaelle; de Crozals, Françoise; Bertrand, Benjamin; Regnier, Véronique; Chevrier, Régine; Streicher, Caroline; Madelaine, Isabelle; Pourroy, Bertrand
Abstract: Introduction: Pharmaceutical consultations is a key point for oral therapy-treated cancer patients' management. Methods: French Society for Oncology Pharmacy built recommendations according to French High Authority of Health regarding the guidelines for Good Practice. Results: Fourteen guidelines were issued and tools proposed to hospital pharmacist's community. Discussion: These guidelines allow to secure management of cancer patients treated by oral therapies. Abstract : Supplemental Digital Content is available in the text